Interdependence of the growth of the Northern Hemisphere ice sheets during the last glaciation: the role of atmospheric circulation - P. Beghin; S. Charbit; C. Dumas; M. Kageyama; D. M. Roche; C. Ritz (Climate of the Past, 2014)
The development of large continental-scale ice sheets over Canada and northern Europe during the last glacial cycle likely modified the track of stationary waves and influenced the location of growing ice sheets through changes in accumulation and temperature patterns. Although they are often mentioned in the literature, these feedback mechanisms are poorly constrained and have never been studied throughout an entire glacial–interglacial cycle. Using the climate model of intermediate complexity CLIMBER-2 coupled with the 3-D ice-sheet model GRISLI (GRenoble Ice Shelf and Land Ice model), we investigate the impact of stationary waves on the construction of past Northern Hemisphere ice sheets during the past glaciation. The stationary waves are not explicitly computed in the model but their effect on sea-level pressure is parameterized. We tested different parameterizations to study separately the effect of surface temperature (thermal forcing) and topography (orographic forcing) on sea-level pressure, and therefore on atmospheric circulation and ice-sheet surface mass balance. Our model results suggest that the response of ice sheets to thermal and/or orographic forcings is rather different. At the beginning of the glaciation, the orographic effect favors the growth of the Laurentide ice sheet, whereas Fennoscandia appears rather sensitive to the thermal effect. Using the ablation parameterization as a trigger to artificially modify the size of one ice sheet, the remote influence of one ice sheet on the other is also studied as a function of the stationary wave parameterizations. The sensitivity of remote ice sheets is shown to be highly sensitive to the choice of these parameterizations with a larger response when orographic effect is accounted for. Results presented in this study suggest that the various spatial distributions of ice sheets could be partly explained by the feedback mechanisms occurring between ice sheets and atmospheric circulation.